Multiscreen Marketing The Seven Things You Need to Know to Reach Your Customers across TVs, Computers, Tablets, and Mobile Phones - Hritzuk, Natasha (Wiley, 2014)
and data exploring how and why consumers navigate across screens as well as real-world examples of consumer-centric multi-screen marketing from companies of all sizes embracing the change. For marketers looking to remain effective in the digital age, Multi-screen Marketing: The Seven Things You Need to Know to Reach Your Customers Across TVs, Computers, Tablets, and Mobile Phones explains how a consumer-centric multi-screen strategy not only simplifies an overly complex and constantly changing marketing landscape, but leads to multi-screen campaigns that connect consumers to brands in meaningful, enduring ways